Community-based social marketing campaign to promote the use of the menstrual cup in Colombian Pacific communities. - Cardozo Baquero, Maria Paula (Kansas State University, 2024)
This report presents a proposal for a Community-Based Social Marketing Campaign aimed at promoting the use of the menstrual cup among the menstruating population of the Colombian Pacific. Menstrual hygiene management is a crucial issue in many vulnerable communities, where social inequality, poverty, and limited access to healthcare pose a significant challenge to the safety, dignity, and survival of these populations. In the absence of communication and education plans that normalize menstruation and menstrual hygiene practices, these communities suffer from adverse impacts on their health, education, and sustainability. Through a collaborative approach that involves local communities, health organizations, educational institutions, and community leaders, this campaign seeks to raise awareness about the benefits of the menstrual cup and overcome the barriers that prevent its adoption to get people to adopt the menstrual cup as the only menstrual hygiene device. Based on Social Diffusion Theory and Community-Based Social Marketing campaign methodology, the campaign employs various community engagement strategies, including educational workshops, peer-to-peer outreach, menstrual cup subsidies, and media campaigns tailored to the community's cultural context. This report develops a proposal composed of 4 steps (behavior selection, identification of barriers and benefits, developing strategies, and recommendations for future implementation). It seeks to understand the problem surrounding menstrual hygiene and propose an effective strategy to increase menstrual cup use. This strategy seeks not only to positively impact the environment by reducing plastic waste but also to improve life in the menstruating population, which currently faces many challenges due to the lack of education about menstrual hygiene.
Keywords: Menstrual cup; Menstruation; Social marketing